Long non-coding ribonucleic acid SNHG18 induced human granulosa cell apoptosis via disruption of glycolysis in ovarian aging - Xuehan Zhao; Feiyan Zhao; Long Yan; Jiaqi Wu; Ying Fang; Cong Wang; Zhimin Xin; Xiaokui Yang (BMC, 2024)
Abstract Background In-depth understanding of dynamic expression profiles of human granulosa cells (GCs) during follicular development will contribute to the diagnostic and targeted interventions for female infertility. However, genome-scale analysis of long non-coding ribonucleic acid (lncRNA) in GCs across diverse developmental stages is challenging. Meanwhile, further research is needed to determine how aberrant lncRNA expression participates in ovarian diseases. Methods Granulosa cell-related lncRNAs data spanning five follicular development stages were retrieved and filtered from the NCBI dataset (GSE107746). Stage-specific lncRNA expression patterns and mRNA-lncRNA co-expression networks were identified with bioinformatic approaches. Subsequently, the expression pattern of SNHG18 was detected in GCs during ovarian aging. And SNHG18 siRNA or overexpression plasmids were transfected to SVOG cells in examining the regulatory roles of SNHG18 in GC proliferation and apoptosis. Moreover, whether PKCɛ/SNHG18 signaling take part in GC glycolysis via ENO1 were verified in SVOG cells. Results We demonstrated that GC-related lncRNAs were specifically expressed across different developmental stages, and coordinated crucial biological functions like mitotic cell cycle and metabolic processes in the folliculogenesis. Thereafter, we noticed a strong correlation of PRKCE and SNHG18 expression in our analysis. With downregulated SNHG18 of GCs identified in the context of ovarian aging, SNHG18 knockdown could further induce cell apoptosis, retard cell proliferation and exacerbate DNA damage in SVOG cell. Moreover, downregulated PKCɛ/SNHG18 pathway interrupted the SVOG cell glycolysis by lowering the ENO1 expression. Conclusions Altogether, our results revealed that folliculogenesis-related lncRNA SNHG18 participated in the pathogenesis of ovarian aging, which may provide novel biomarkers for ovarian function and new insights for the infertility treatment.